Viral Infections and Spontaneous Abortion in Women: A Case-Control Study - Maryam Yarabbi; Mohsen Nakhaie; elham Jafari Maskouni; Elham Mousavi; narges karimi; Ali Mohammad Arabzadeh; nasim Pordamghan; Saeedeh Ebrahimi (Journal of Kerman University of Medical Sciences)
Background: Spontaneous abortion before the 20th week, a prevalent pregnancy complication, is often linked to intrauterine viral infections. This study aims to identify DNA viruses in placental tissue from women with spontaneous abortion and full-term pregnancies, establishing a correlation with first-trimester spontaneous abortion.Methods: This case-control study was conducted in Kerman city between 2021 and 2022. Placental tissue samples were collected from 50 women who had experienced spontaneous abortion in the first trimester and 50 women with normal pregnancies. The PCR method was employed to assess the presence of specific viruses.Results: In the case group, the average age was 28.74±6.11, while in the control group, it was 31.08±6.48. The study identified cytomegalovirus (CMV), human papillomavirus types (HPV) 16 and 18, herpes simplex virus-1 (HSV-1), and herpes simplex virus-2 (HSV-2) genomes in varying percentages in the case group compared to the control group. Notably, the parvovirus B19 genome was not detected in either group. However, statistical analysis did not indicate a significant difference in the presence of these viruses between the case and control groups.Conclusion: Consistent with some prior research, this study did not find a correlation between viral placental infections and an increased risk of spontaneous abortion. Further research should be conducted with larger sample sizes across different regions to ascertain the true role of viral infections in abortion.